Sensitization to latex and food allergens in atopic dermatitis patients according to ALEX2 Allergy Xplorer test - Čelakovská, J; Čermákova, E; Andrýs, C; Boudkova, P; Krejsek, J (Molecular immunology, 2024)
UNLABELLED: Aim of our study is to analyse the sensitisation profile to molecular components of latex and of food allergens with the use of ALEX2 Allergy Xplorer test and to compare these results with the anamnestical data after latex exposure and with the anamnestical data after exposure to food allergens in atopic dermatitis patients. METHODS: 100 patients were included in the study (49 men and 51 women with the average age 40.6 years). The specific IgE was examined with the use of ALEX2 Allergy Xplorer test. A detailed personal history of allergic reaction to latex and allergic reaction to food allergens was taken in all included patients. RESULTS: The sensitisation to latex was recorded in 17 % of patients, majority of patients have positive results of specific IgE to Hev b 8 without clinical reaction to latex. In 7 % of patients with positive results of specific IgE to Hev b 1, Hev b 3, Hev b 5, Hev b 6.02 and Hev b 11 the contact urticaria or contact dermatitis were recorded. The latex fruit syndrome was recorded in 7 % of patients; in another 10 % of patients we recorded no clinical reaction to latex, but the positive results to molecular components of latex and the clinical symptoms after ingestion of different kinds of fruits. CONCLUSION: The significant relation between the results of specific IgE to molecular components Hev b 3, Hev b 5 and Hev b 6.02 and the clinical reaction to latex was confirmed; these components significantly imply clinical reactivity to latex.
Keywords: senioři; potravinová alergie; Immunoglobulin E; Atopic dermatitis; Latex allergy; mladiství; Middle Aged; Allergens; mužské pohlaví; Food Hypersensitivity; Adult; mladý dospělý; Latex; Dermatitis, Atopic; Young Adult; alergeny; ženské pohlaví; Humans; latex; imunoglobulin E; alergie na latex; lidé středního věku; Molecular components; atopická dermatitida; dospělí; Female; Aged; Latex Hypersensitivity; Adolescent; lidé; Male